2020
DOI: 10.3390/polym12081655
|View full text |Cite
|
Sign up to set email alerts
|

DLP 3D Printing Meets Lignocellulosic Biopolymers: Carboxymethyl Cellulose Inks for 3D Biocompatible Hydrogels

Abstract: The development of new bio-based inks is a stringent request for the expansion of additive manufacturing towards the development of 3D-printed biocompatible hydrogels. Herein, methacrylated carboxymethyl cellulose (M-CMC) is investigated as a bio-based photocurable ink for digital light processing (DLP) 3D printing. CMC is chemically modified using methacrylic anhydride. Successful methacrylation is confirmed by 1H NMR and FTIR spectroscopy. Aqueous formulations based on M-CMC/lithium phenyl-2,4,6-trimethylben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…Moreover, the 3D-printed gels showed their potentialities in sustained-release drugs (i.e., lactoferrin) up to 21 days at optimum pH conditions. Melili et al (2020) [ 236 ] reported a photocurable bio-ink based on methacrylate-CMC that showed optimum potentialities to produce 3D-shaped hydrogels with good mechanical properties and swelling behavior. However, in that study, the authors revealed the applicability of CMC-based biomaterials in the bio-printing process via the digital light processing (DLP) method.…”
Section: Application Of Cmcmentioning
confidence: 99%
“…Moreover, the 3D-printed gels showed their potentialities in sustained-release drugs (i.e., lactoferrin) up to 21 days at optimum pH conditions. Melili et al (2020) [ 236 ] reported a photocurable bio-ink based on methacrylate-CMC that showed optimum potentialities to produce 3D-shaped hydrogels with good mechanical properties and swelling behavior. However, in that study, the authors revealed the applicability of CMC-based biomaterials in the bio-printing process via the digital light processing (DLP) method.…”
Section: Application Of Cmcmentioning
confidence: 99%
“…[ 38 ] Terpenes, such as linalool monomer and a prepolymer from limonene [ 39 ] and polymyrcene mixed with reactive diluent β‐myrcene, [ 40 ] were used to print porous structures with high ductility following thiol‐ene chemistry. Methacrylated chitosan, [ 41,42 ] starch [ 43 ] and carboxymethyl cellulose [ 44 ] have also been used to print hydrogels, and good biocompatibility has been reported. Moreover, silk fibroin modified with methacrylates was applied in DLP printing to fabricate scaffolds and mimicked organ shapes with excellent biocompatibility.…”
Section: Biobased Photopolymersmentioning
confidence: 99%
“…To overcome agglomeration problems, in the literature, good results have been obtained on a laboratory scale, with some trials in a semi-industrial scale [20][21][22][23] or even in 3D printing [24], using environmentally unfriendly solvents or chemicals (acetone, methanol, acetic acid, chloroform, sulphuric acid, dimethyl acetamide, and lithium chloride), making the industrial-scale production of MFC-based biocomposites difficult and unsustainable.…”
Section: Introductionmentioning
confidence: 99%